Draft Genome Sequence of Oceanobacillus jordanicus Strain GSFE11, a Halotolerant Plant Growth-Promoting Bacterial Endophyte Isolated From the Jordan Valley. (January 2022) - Alhindi, Tareq; Albdaiwi, Randa
The bacterium Oceanobacillus jordanicus strain GSFE11 is a halotolerant endophyte isolated from sterilized roots of Durum wheat ( Triticum turgidum ssp. Durum ) growing in hot and arid environments of Ghor Safi area in the Jordan Valley. The draft genome sequence and annotation of this plant growth-promoting endophytic bacterium are reported in this study. The draft genome sequence of Oceanobacillus jordanicus strain GSFE11 has 3 839 208 bp with a G + C content of 39.09%. A total of 3893 protein-coding genes and 68 RNA coding genes were predicted. Several putative genes that are involved in secretion and delivery systems, transport, adhesion, motility, membrane proteins, plant cell wall modification, and detoxification were identified, some are characteristics of endophytes lifestyle including genes that are involved in metabolism of carbohydrate, genes for xylose, fructose and chitin utilization, quinone cofactors biosynthesis, genes associated with nitrogen, sulfur, phosphate and iron acquisition, in addition to genes involved in the biosynthesis of plant hormone auxin. This study highlights the importance of using genome analysis and phylogenomic analysis to resolve the differences between closely related species, such analysis showed Oceanobacillus jordanicus strain GSFE11 to be a new species closely related to Oceanobacillus picturae (genome size 3.67 Mb), Oceanobacillus jordanicus has higher a number of predicted genes compared with Oceanobacillus picturae (3961 genes vs 3823 genes).